2021
DOI: 10.1016/j.isci.2021.102757
|View full text |Cite
|
Sign up to set email alerts
|

Extensive three-dimensional intratumor proteomic heterogeneity revealed by multiregion sampling in high-grade serous ovarian tumor specimens

Abstract: HighlightsLMD was used to investigate 3-D molecular heterogeneity in ovarian cancer tissue Diverse molecular profiles were identified from 3-D spatially separated samples Molecular heterogeneity impacts HGSOC prognostic sub-type assignment Proteomic heterogeneity analysis web portal deployed at www. lmdomics.org

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(74 citation statements)
references
References 75 publications
15
59
0
Order By: Relevance
“…Some evidence supports the existence of spatially distinct intratumoral subpopulations, suggesting that such resolution may be possible with systematic workflows capable of elucidating the organization and spatial distribution of such subpopulations. In support of this, recent studies using spatial profiling techniques have demonstrated stark differences in biological activity between spatially separated regions of solid tumors and tumor microenvironments [14,17,19–21]. Notably, spatially heterogeneous tumoral subpopulations have been identified at the protein level, with the degree of proteomic heterogeneity predictive of therapeutic response [14,15].…”
Section: Addressing Spatial Proteomic Intratumoral Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence supports the existence of spatially distinct intratumoral subpopulations, suggesting that such resolution may be possible with systematic workflows capable of elucidating the organization and spatial distribution of such subpopulations. In support of this, recent studies using spatial profiling techniques have demonstrated stark differences in biological activity between spatially separated regions of solid tumors and tumor microenvironments [14,17,19–21]. Notably, spatially heterogeneous tumoral subpopulations have been identified at the protein level, with the degree of proteomic heterogeneity predictive of therapeutic response [14,15].…”
Section: Addressing Spatial Proteomic Intratumoral Heterogeneitymentioning
confidence: 99%
“…In support of this, recent studies using spatial profiling techniques have demonstrated stark differences in biological activity between spatially separated regions of solid tumors and tumor microenvironments [14,17,19–21]. Notably, spatially heterogeneous tumoral subpopulations have been identified at the protein level, with the degree of proteomic heterogeneity predictive of therapeutic response [14,15]. While these comprehensive high‐resolution spatial analyses emphasize the need for routine spatial profiling, their current forms are often not feasible to be used routinely in clinical practice due to cost, subjectivity in region selection by different observers, and practical considerations.…”
Section: Addressing Spatial Proteomic Intratumoral Heterogeneitymentioning
confidence: 99%
“…As described in the preanalytical section, tumor samples frequently exhibit distinct subclones within tumors, and any given result will be a synthesis of these subclones according to their relative proportions [ 66 , 67 , 68 ]. By definition, a biopsy represents only a fraction of the tissue at the site.…”
Section: Hrd Evaluation In Clinics: Current Limitationsmentioning
confidence: 99%
“…Cells of interest in a tissue section are recognized by a microscope, cut out by a laser, and then collected for subsequent analysis. Hunt et al (2021) [ 19 ] demonstrated the benefits of investigating tumor tissue applying LCM in a 3-dimensional fashion. In this manner, detailed insights into tumor microenvironment heterogeneity are obtained, thereby getting access to prognostic signatures (biomarkers) and molecular cancer pathophysiology [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hunt et al (2021) [ 19 ] demonstrated the benefits of investigating tumor tissue applying LCM in a 3-dimensional fashion. In this manner, detailed insights into tumor microenvironment heterogeneity are obtained, thereby getting access to prognostic signatures (biomarkers) and molecular cancer pathophysiology [ 19 ]. However, LCM is very time-consuming.…”
Section: Introductionmentioning
confidence: 99%